Severe Pelvic Fracture in the Elderly: High Morbidity, Mortality, and Resource Utilization. Issue 10 (26th October 2020) - Garcia, Monika; Firek, Matthew; Zakhary, Bishoy; Brenner, Megan; Hildebrand, Frank; Coimbra, Raul
Severe pelvic fractures (PF) in the elderly are common and analysis of outcomes and resource utilization are lacking. Using the National Trauma Databank (2007-2016), 13 267 patients aged ≥65 years with severe PF (Abbreviated Injury Scale [AIS] pelvis ≥3; AIS 3 = 10 388; AIS 4 = 2124; AIS 5 = 805) were studied. Demographic data, management, resource utilization, complications, and mortality were analyzed for each group. Data are represented as % or median interquartile range (IQR). Multivariate logistic regression analyzed risk factors for mortality, Intensive Care Unit (ICU) admission, and ventilator use. Median age was 77, and most of them were females (59%). Falls occurred in 52%, motor vechicle crash in 21.5%, and pedestrian struck in 11.6%. Median injury severity score was 16 (IQR: 9, 27). Shock on admission (9.4%) increased with injury severity. Glasgow Coma Scale < 8 occurred in 8%. Blood transfusion increased with injury severity (17%, 29%, and 51%). Angiography occurred in 9%, external fixation in 4%, internal fixation in 16%, and pelvic packing in 1%, the majority in the AIS 5 group. Overall, 46% required ICU admission and 30% underwent mechanical ventilation; median Hospital Length of Stay was 6 (IQR 4, 11), ICU length of stay was 5 (IQR 2, 10), and median ventilator days were 4 (IQR 1-11). Mortality rate was 13.3% (AIS 3 = 10%, AIS 4 = 19%, and AIS 5 = 44%).Severe PF in the elderly is associated with high resource utilization, complications, and mortality.